Experimento para medir distâncias utilizando o arduino como proposta didática para o ensino de física - CARVALHO, Matheus de Souza (2023)
From the observation of obsolete methods that produce a less encouraging teaching for the students, it was verified the necessity of the production of this study. The aim is to show that physics can be taught more attractively using active learning methods, for this study presents an experiment that uses the Arduino platform and the HC-SR04 sensor to measure distances and thus contribute to the teaching of physical. The components of the experiment are shown and their construction is taught in step-bystep format showing their details. The source code to be used in the experiment is shown along with the physical concepts involved. It is hoped with this study that the teaching of physics goes hand in hand with new technologies in order to overcome conservative teaching methods.